Differences in phase transformation in laser peened and shot peened 304 austenitic steel. (15th June 2020) - Starman, Bojan; Hallberg, Håkan; Wallin, Mathias; Ristinmaa, Matti; Halilovič, Miroslav
Highlights: Numerical models of laser shot peening (LSP) and conventional shot peening (SP), capable of predicting residual stresses and phase transformation, are presented. It is shown that the main reason for significantly more martensite being formed in 304 stainless steel during SP, compared to LSP, is the strain-stress state dependence of the phase transformation. Numerical analyses predict significant differences in martensite formation during SP and LSP, which is frequently observed in experiments. Abstract: Laser Shock Peening (LSP) and Shot Peening (SP) are processes used to mechanically alter the surface properties of metals by inducing a transient high-pressure wave by a laser pulse or by a high-velocity impact of a peening particle. Both processes aim to induce compressive residual stresses near the surface and the level of residual stresses obtained from SP or LSP is similar. When austenitic steel is peened, martensitic phase transformation takes place. It has been observed in experiments that the amount of martensite in shot-peened surfaces is significantly higher than in laser peened surfaces. The cause of these differences is, however, not yet fully explained and the available explanations are often conflicting. In this study, both SP and LSP are modelled using an elasto-viscoplastic model that also account for martensitic phase transformation. The analyses show that LSP and SP are fundamentally different from a mechanical point of view. By tracing the stress trajectories in the principal stress space, it is shown that martensite formation and plastic straining are highly dependent on the intensity of the individual components of hydrostatic and deviatoric stress, which evolve differently in the two processes. Graphical abstract: Image, graphical abstract